PENGARUH GAYA HIDUP, HARGA, PROMOSI,CITRA MEREK, DAN VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO (Studi Kasus pada konsumen pengguna Oppo, Tiga Putra Handphone Center Kota Malang) - Lusi Agustina; Rois Arifin; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               This study aims to examine and analyze the influence of lifestyle, price, promotion, brand image and viral marketing on Oppo smartphone purchasing decisions. Population and sample are 80 Oppo smartphone users. Data collection through questionnaires. Data analysis in this study uses the help of SPSS version 14. application testing data used in this study include validity test, reliability test, Normality test, multiple linear regression analysis, classical assumption test, and testing the research hypothesis.               The results of the analysis show that partially viral marketing has a significant effect on the purchasing decisions of Oppo smartphones while Lifestyle, Price, Promotion, Brand image have no significant effect on Oppo's smartphone purchasing decisions. And together (simultaneous) shows that lifestyle, price, promotion, brand image and viral maeketing variables influence Oppo smartphone purchasing decisions. Keywords: Lifestyle, Price, Promotion, Brand Image and Viral Marketing.